Genome-wide identification of WRKY gene family and expression analysis of key WRKY genes in response to Fusarium solani infection in Lycium barbarum - Wu, Xia; Li, Nan; Wang, Bin; Chen, Wei; Zhang, Chongqing; Sun, Yuyan; He, Jing (Frontiers in Plant Science, 2025)
Wolfberry (Lycium barbarum), a member of the Solanaceae family, is recognized as a pioneering tree species for afforestation in saline-alkali soils and holds significant economic value as a forest species. Its fruit is abundant in bioactive compounds that contribute in both ecological health and human well-being. The WRKY gene family has been extensively studied across various species, with its members’ functions increasingly elucidated. However, limited research has focused on the role of the WRKY genes of L. barbarum, particularly in resistance to root rot. This study identified the bioinformatics of 104 WRKY genes in wolfberry, encompassing phylogenetics, conserved motifs, gene structures, synteny, and collinearity. Based on structural and phylogenetic, the 104 LbWRKYs are divided into three main groups, Group I, II and III, with 26, 62 and 15 members, respectively. Synteny analysis revealed high homology between LbWRKY and tomato SlWRKY, with a total of 117 pairs of homologous genes identified. Cis-acting elements analysis demonstrated that subgroup II LbWRKY genes contained a higher number of plant hormone-related regulatory elements. Furthermore, 28 LbWRKY genes were found to respond to the infection of Fusarium solani. Protein-protein interaction prediction and correlation analyses revealed that associations between LbWRKY genes and flavonoid and phenylpropanoid synthesis-related genes, and the results showed that LbWRKY8/100/63/84/102/42/45 was involved in the mechanism of root rot resistance. Expression analysis following Fusarium solani inoculation confirmed that these genes participate in root rot resistance in L. barbarum. This study provides valuable insights into the functional roles of LbWRKY genes, and establishing a foundation for future research on their involvement in secondary metabolite synthesis and their role in enhancing the disease resistance of L. barbarum.